Clinical Heterogeneity in ME/CFS. A Way to Understand Long-COVID19 Fatigue - Murga, Iñigo; Aranburu, Larraitz; Gargiulo, Pascual A.; Gómez Esteban, Juan Carlos; Lafuente, José-Vicente (Frontiers in Psychiatry, 2021)
The aim of present paper is to identify clinical phenotypes in a cohort of patients affected of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome. Ninty-nine patients and twenty-two healthy controls were studied with the following questionnaires, in addition to medical history: visual analogical scale for fatigue and pain, DePaul questionnaire (post-exertional malaise, immune, neuroendocrine), Pittsburgh sleep quality index, COMPASS-31 (dysautonomia), Montreal cognitive assessment, Toulouse-Piéron test (attention), Hospital Anxiety and Depression test and Karnofsky scale. Co-morbidities and drugs-intake were also recorded. A hierarchical clustering with clinical results was performed. Final sample was made up of 84 patients, mean age 44.41±9.37 years (66 female/18 male) and 22 controls, mean age 45±13.15 years (14 female/8 male). Patients meet diagnostic criteria (Fukuda-1994 and/or Carruthers-2011). Clustering analysis identify five phenotypes. Two groups without fibromyalgia were differentiated by various levels of anxiety and depression (13 and 20 patients). The other three presenting fibromyalgia plus one without it, but with high scores in pain scale, were segregated by prevalence of dysautonomia (17), neuroendocrine (15) and immunological affectation (19). Regarding gender, women showed higher cognitive scores tan men, referred higher pain levels and worse symptoms of depressive syndrome compared to men. Mathematical tools are a suitable approach to make objective the evaluations of some elusive features in order to understand the syndrome. Clustering unveil phenotypes combining fibromyalgia with varying degrees of dysautonomia, neuroendocrine or immune features and absence of fibromyalgia with high or low levels of anxiety-depression. There is no a specific phenotype for women or men.